Cytolytic Effect of Newcastle Disease Virus Strain V4 (UPM) on Leukemic Cell Lines Cem-Ss and Hl 60 - Zawawi, Madihah (2006)

(untitled)
Newcastle disease virus (NDV) was classified into the order Mononegalavirales, family Paramyxoviridae, su b-famil y Paramyxovirinae and genus Avulavirus. The genome consists of a single stranded, non-segmented, enveloped negative sense RNA which consists of about 15 kb, encoding six viral proteins which are the phosphoprotein (P), matrix protein (M), fusion protein (F), hemagglutinin-neuraminidase protein (HN), polymerase (L) and nucleoprotein (NP). NDV causes a highly contagious, generalized virus disease of domestic poultry and wild birds but only mild conjunctivitis and laryngytis in humans. Inoculation of live NDV strain V4(UPM), a local heat resistant variant of the Queensland vaccine strain, V4HR, showed visible cytolytic effects on CEM-SS and HL-60 leukemic cells. Therefore, three approaches were taken to study the effect of V4 (UPM) against the two leukemic cell lines which are via morphological observation, cytopathic effect and biochemical study. The morphological changes observed via inverted light microscopy include cell shrinkage and blebbing of the cell membrane as well as membrane-bound apoptotic bodies. Results obtained from microtetrazolium cytotoxicity assay showed a titre of 110.6 and 150.9 HAUIml of the virus reducing the cell population to 50% viability for HL 60 and CEM-SS, respectively. The virus affects cell proliferation in a way that it reduces viability abruptly at 24 hours postinoculation in HL 60 cell population while in CEM-SS cell population proliferation was inhibited almost immediately after inoculation. Morphological observation using the differential uptake of acridine orange and propidium iodide dyes showed the cells were undergoing apoptosis. The early apoptotic cells which which had intact membranes but have started to fragment their DNA, still had green cytoplasm and nuclei but condensation of the chromatin were visible as bright green patches at the brim of the nucleus membrane. lnvagination of plasma membrane or blebbing appearance on the cell surface was also apparent. Late apoptosis showing bright red cells surrounded with apoptotic bodies were also observed in cell populations inoculated with the virus. The DNA of infected CEM-SS and HL 60 cells produced a DNA laddering profile on agarose-gel electrophoresis, a biochemical marker which is frequently regarded as the biochemical hallmark of apoptosis. Electron microscopy also confirmed the morphological structures indicating apoptosis was involved in the death of cells treated with the virus. In conclusion, based on the findings of these experiments, the mechanism by which live NDV strain V4(UPM) can induce cytolysis in CEM-SS and HL-60 cells is via apoptosis. Thus, it may be possible to further develop V4(UPM), a local oncolytic NDV vaccine strain, for the future choice of treatment in cancer patients